Cluster Preface: C–O And Related Bond Activation - Tobisu, Mamoru; Chatani, Naoto; Snieckus, Victor (Synlett, 2017)
Mamoru Tobisu received his PhD from Osaka University under the direction of Prof. Shinji Murai (2001). During his PhD studies, he was a visiting scientist (1999) with Prof. Gregory C. Fu at MIT. Following a period as a scientist at the Takeda Pharmaceutical Company (2001–2005), he started his academic career at Osaka University in 2005 as an assistant professor with Prof. Naoto Chatani. He was then appointed as an associate professor at the Center for Atomic and Molecular Technologies at Osaka University (2011) and was promoted to full professor at the Department of Applied Chemistry of Osaka University (2017). He received the Thieme Chemistry Journals Award (2008), the Chemical Society of Japan Award for Young Chemists (2009), the Young Scientists’ Award, a Commendation for Science and Technology from the Minister of Education, Culture, Sports, Science and Technology (2012), the Merck-Banyu Lectureship Award (2012), Thomson Reuters Research Front Award (2016), and the Mukaiyama Award (2018). Naoto Chatani received his PhD in 1984 under Professors Noboru Sonoda and Shinji Murai. In 1984, he joined the Institute of Scientific and Industrial Research at Osaka University as an Assistant Professor in the laboratory of Professor Terukiyo Hanafusa. After postdoctoral studies (1988–1989 under Professor Scott E. Denmark at the University of Illinois, Urbana-Champaign), he moved back to Osaka University and was promoted to the rank of Associate Professor (1992) and to Full Professor (2003). He is a recipient of The Chemical Society of Japan Award for Young Chemists (1990), The Green & Sustainable Chemistry Award from the Minister of Education, Culture, Sports, Science and Technology (2005), the Nagoya Silver Medal (2013), The Chemical Society of Japan Award (2017), a Humboldt Research Award (2017), a Clarivate Analytics Highly Cited Researcher (2017) and will be a recipient of an Arthur C. Cope Scholar Award (2018). Victor Snieckus was born in Kaunas, Lithuania and spent his childhood in Germany during World War II. He received training at U. Alberta, Canada, (B.Sc.), U. California, Berkeley (M.Sc. D.S. Noyce), and U. Oregon (Ph.D. Virgil Boekelheide). He returned to his adopted country for postdoctoral studies (National Research Council, Ottawa, Ted Edwards). Appointments: U. of Waterloo, Assistant (1966) to Professor (1979); Monsanto/NRC Industrial Research Chair, 1992–1998; Queen’s University, Inaugural Bader Chair in Organic Chemistry (1998–2009); Bader Chair Emeritus and Director, Snieckus Innovations, 2009-. Selective awards: A.C. Cope Scholar (2001, one of 5 Canadians), Order of the Grand Duke Gediminas (2002, from the President of Lithuania), Arvedson-Schlenk (2003, Gesellschaft Deutscher Chemiker), Bernard Belleau (2005, Canadian Society for Chemistry), Givaudan-Karrer Medal (2008, U. Zurich), Honoris causa (2009, Technical U. Tallinn, Estonia), Global Lithuanian Award (2012), Yoshida Lectureship (2017). He hopes that he has only temporarily discontinued playing hockey and wishes also to return to the clarinet.